PENGARUH ASUPAN SUSU FORMULA TERHADAP BERAT BADAN DAN TINGGI BADAN SANTRI - Priyono, Putri Kusumawati; Fatayati, Aminatul; Maryanti; Dian Galih Latifah (INVOLUSI: Jurnal Ilmu Kebidanan, 2024)
Milk manifests a food that contains nutrients such as carbohydrates, proteins, fats and minerals, which are beneficial for the growth and development of the child. The level of consumption of milk in Indonesia is still relatively low. Based on the Central Statistics Agency( BPS), Indonesia's per capita milk consumption is only 12.1 liters per year, far below the Finnish average of 361 liters. The National stunting rate (by height / age) of children aged 5-12 is 30.7% (12.3% very short, 18.4% short) the underweight rate in children aged 5-12 is 11.2%, of which 4.0% are very underweight and 7.2% are very underweight. It aims to determine the effect of milk intake on height and weight gain in school-age children. The experimental study of 20 subjects was divided into 10 control subjects. The treated subjects drank 250 ml of low-fat, high-calcium UHT milk per day for 60 days, while the controls did not eat. In this study, an Independent t-test was used to test the effect of milk on height, and the Mann- Whitney U-test was used to test the effect of milk on weight. P = 0.000 was obtained by independent T-test and P = 0.989 by Mann-Whitney U-test. The results of the study indicate that milk intake affects the growth of height, not weight in school-age children.